STUDENTS’ ANXIETY IN CLASS PRESENTATION ACTIVITY AT THE POSTGRADUATE ENGLISH EDUCATION STUDY PROGRAM OF THE UNIVERSITY OF BENGKULU - HAYADI, ALGRIN; AZWANDI, AZWANDI; HARAHAP, ALAMSYAH (Linguists : Journal of Linguistics and Language Teaching, 2023)
Students’ anxiety can impact the learning process. Anxiety causes students to overthink and focus on the negative, such as the fear of failing, getting lost in thought about a topic, or being laughed at or ashamed by others because of a mistake. Feeling anxious makes students not know what to say while they speak in front of the class. They forget all of the words they already know, which causes them to become stuck in the middle of the presentation, and, as a result, the presentation will not run smoothly. Students will be frustrated, ashamed, hopeless, and defeated as a result of this situation. Additionally, the students are unable to achieve the anticipated learning goal. If anxiety always occurs when learning a foreign language, especially in English presentation classes, it will certainly be a very serious problem for students. As a result, it is critical to investigate, and the goal of this study is to: (1) learn about the anxiety levels experienced by postgraduate students of the English Education study program in Bengkulu. (2) reveal what factors significantly influence students' anxiety level in class presentations, and (3) reveal the methods that first-semester students of Bengkulu University's postgraduate program in English education use to reduce their anxiety. The subjects of this research were the 21 students of the first semester of the postgraduate English program at Bengkulu University, and to fulfil these research objectives, the descriptive qualitative research design was utilized in this study. In this study, the researchers collected data using instruments such as a questionnaire and an interview. After conducting the research, the results revealed that most students are at an "anxious" level, and the researchers found that there are three main factors that significantly influence their anxiety. They are communication apprehension, test anxiety, and fear of evaluation, and in order to overcome their anxiety, students have their own ways, such as being well prepared and practicing as much as possible, not overthinking, holding something, doing physical movements, and relaxing.